Periprostatic lidocaine infiltration versus transrectal lidocaine gel for local anaesthesia in transrectal ultrasound guided prostate biopsy - Christopher CKH; Goh EH; Praveen S; Zulkifli MZ (Department of Surgery, UKM Medical Centre, 2011)
Management of pain plays an important role during prostate biopsy. Various types of management of pain plays an important role during prostate biopsy. Various types of anaesthetic methods have been used. The present study aimed to compare the efficacy and complication rate between periprostatic lidocaine infiltration and transrectal lidocaine gel in transrectal ultrasound guided prostate biopsy. All prostate biopsy patients were included except those with lidocaine, allergy, haemorrhagic diathesis, anticoagulation therapy, the inability to rate a visual analogue scale and inability to obtain consent. They were randomized into two groups. Group 1 received 20ml 2% transrectal lidocaine gel. Group 2 received 5ml 1% lidocaine infiltration for each periprostatic nerve block with 23-gauge spinal needle. After three minutes, prostate biopsy was performed with an 18 gauge 7-inch spring-loaded biopsy gun. Six biopsies were taken for each lobe. Pain during probe insertion, biopsy and immediately after the procedure was assessed using the Visual Analogue Scale. Any complication immediately after procedure, one day or after one week, was recorded. Mean pain score was lower after periprostatic lidocaine infiltration compared to transrectal lidocaine gel (3.1 + 1.9 versus 4.9 + 2.4, p = 0.027). There was no statistically significant difference in the complication rate. Transrectal ultrasound prostate biopsy using periprostatic lidocaine infiltration provides better anaesthesia as compared to the transrectal lidocaine gel application with no significant difference in complication. Thus, the use of periprostatic lidocaine infiltration in TRUS guided prostate biopsy is recommended.